International organizations and member state responsibility : critical perspectives - Barros, Ana Sofia; Ryngaert, Cedric; Wouters, Jan, 1964- (Nova et vetera iuris gentium, 2017)
"[This book] is the first international public law book entirely devoted to the topic of member state responsibility. Throughout its ten contributions, it takes stock of the legal developments brought about by the International Law Commission s work on international responsibility, and critically unveils the major remaining conceptual gaps in the field. The novel approaches offered in the book serve as a repository of the various understandings within academia and legal practice that reflect the evolution of the contemporary law of international (member state) responsibility."--